Use of cork powder and granules for the adsorption of pollutants: a review. - Pintor, Ariana M A; Ferreira, Catarina I A; Pereira, Joana C; Correia, Patrícia; Silva, Susana P; Vilar, Vítor J P; Botelho, Cidália M S; Boaventura, Rui A R (Water research, 2012)
Cork powder and granules are the major subproducts of the cork industry, one of the leading economic activities in Portugal and other Mediterranean countries. Many applications have been envisaged for this product, from cork stoppers passing through the incorporation in agglomerates and briquettes to the use as an adsorbent in the treatment of gaseous emissions, waters and wastewaters. This paper aims at reviewing the state of the art on the properties of cork and cork powder and their application in adsorption technologies. Cork biomass has been used on its original form as biosorbent for heavy metals and oils, and is also a precursor of activated carbons for the removal of emerging organic pollutants in water and VOCs in the gas phase. Through this literature review, different potential lines of research not yet explored can be more easily identified.
Keywords: activated carbon; Adsorption; Cork granules; cork powder; Heavy metals; Pollutants